Jerry OKeefe on O'Keefes Path - Branch Cultural Historical Association (2008)
As the trees closer to the Place were cut, paths were required to haul out timber and firewood from further away. Along the first paths, wood was carried out on a horse and slide in the winter. Paths were blazed by individuals but used by all. OKeefes (Keefes) Path is a recent slide path cut by Jerry OKeefe. Other slide paths include Joe Nashs Slide Path, Franks Path and Paddys Path.